The New Role of Notaries in Making Information on Inheritance Rights after the New Enactment - Soni Hana Fika; Dahniarti Hasana (Sultan Agung Notary Law Review, 2022)
. This study aims to determine and analyze the authority of the Balai Harta Peninggalan in making information on inheritance rights after the enactment of Permenkumham No. 7 of 2021, the roles and responsibilities of Notaries in the implementation of making inheritance rights after the enactment of Permenkumham No. 7 of 2021. The use of the sociological juridical approach in legal research is caused by problems that are closely studied with juridical and sociological factors. The analytical knife in answering the problem formulation uses the theory of certainty and the theory of authority. The results of the study indicate that the authority of the Balai Harta Peninggalan in making a certificate of inheritance after the enactment of Permenkumham No. 7 of 2021 has been regulated in Article 3 letter c, in carrying out BHP's obligations to carry out the function of making an inheritance certificate. However, in Permenkumham No. 7 of 2021, it is not explained who can make a certificate of inheritance at the BHP. The role of the Notary in the implementation of making inheritance rights after the enactment of Permenkumham No. 7 of 2021, namely making inheritance rights in accordance with the stipulated requirements and procedures for making inheritance certificates. Notaries must ensure the process of inheritance distribution for the use of groups and parties involved in the distribution of inheritance. The notary in making the certificate of inheritance is responsible for the village and sub-district if the SKWH does not appear in the deed. However, there are SKHWs of Chinese descent which are the obligation of a notary, because they use a Notary SKHW. And depending on the request or the needs of the client itself. Do you want SKWH or take a notary deed.